2008
DOI: 10.1073/pnas.0808488105
|View full text |Cite
|
Sign up to set email alerts
|

Striatal progenitors derived from human ES cells mature into DARPP32 neuronsin vitroand in quinolinic acid-lesioned rats

Abstract: Substitutive cell therapy using fetal striatal grafts has demonstrated preliminary clinical success in patients with Huntington's disease, but the logistics required for accessing fetal cells preclude its extension to the relevant population of patients. Human embryonic stem (hES) cells theoretically meet this challenge, because they can be expanded indefinitely and differentiated into any cell type. We have designed an in vitro protocol combining substrates, media, and cytokines to push hES cells along the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
272
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(280 citation statements)
references
References 30 publications
4
272
4
Order By: Relevance
“…Tumor formation and graft overgrowth [45][46][47] from pluripotent stem cells and their derivatives are major hurdles for the application of stem cell therapy in stroke and other brain diseases. In previous studies, human iPSCs showed high tumorigenicity after intracerebral implantation in stroke-damaged brain [24].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor formation and graft overgrowth [45][46][47] from pluripotent stem cells and their derivatives are major hurdles for the application of stem cell therapy in stroke and other brain diseases. In previous studies, human iPSCs showed high tumorigenicity after intracerebral implantation in stroke-damaged brain [24].…”
Section: Discussionmentioning
confidence: 99%
“…Aubry et al [40] first described the differentiation of hESCs into medium spiny neurons in vitro, and their integration in vivo following xenotransplantation into adult rats. To achieve this goal, the authors adopted a 3-stage in vitro protocol for generating medium spiny neurons, using agents identified as critical for the in vivo development of these cells.…”
Section: Embryonic Stem Cells As a Source Of New Medium Spiny Neuronsmentioning
confidence: 99%
“…First, ES-derived grafts have been reported to induce formation of teratomas or neuroepithelial tumors [41]. The formation of these tumors is a function of the degree to which the cells are selectively enriched and differentiated prior to transplantation [40,42]. However, embryoid bodies (EBs) from early stage of the culture can be contaminated with undifferentiated multipotent cells that escaped the differentiation process, permitting teratogenesis in the host [41][42][43][44].…”
Section: Embryonic Stem Cells As a Source Of New Medium Spiny Neuronsmentioning
confidence: 99%
“…First, hNPCs differentiate much slower than their rodent counterparts [16][17][18]. As a consequence, prolonged proliferation was observed in vivo and eventually led to graft overgrowth [19,20], with deleterious consequences on the host tissue cytoarchitecture. Second, hNPCs undergo decreased neurogenesis upon expansion in vitro [21,22], which might limit the potential benefit for neuronal replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been tested to overcome these obstacles, including prospective isolation of desired cell types [23][24][25][26] and commitment of hNPCs toward the relevant lineage by epigenetic stimulation [12,13,16,19,[27][28][29][30][31]. A strategy that has more recently emerged consists of genetic induction of neural stem cell differentiation toward a particular phenotype.…”
Section: Introductionmentioning
confidence: 99%